M|G|∞ system parameters for a particular collection of service time distributions - Ferreira, M. A. M. (6th International Conference APLIMAT 2007, 2007)
In this paper we present the problems that arise when we compute the moments of service time distributions, for which the M|G|∞ busy period and busy cycle become very easy to study. We show how to overcome them. We also compute the busy cycle renewal function and the "peak" and the "modified peak" for the M|G|∞ busy period and busy cycle in the case of those service time distributions.